Test-retest reliability of high-resolution surface electromyographic activities of facial muscles during facial expressions in healthy adults: A prospective observational study - Trentzsch, Vanessa; Mueller, Nadiya; Heinrich, Martin; Kuttenreich, Anna-Maria; Guntinas-Lichius, Orlando; Volk, Gerd Fabian; Anders, Christoph (Frontiers in Human Neuroscience, 2023)
Objectives: Surface electromyography (sEMG) is a standard method for psycho-physiological research to evaluate emotional expressions or in a clinical setting to analyze facial muscle function. High-resolution sEMG shows the best results to discriminate between different facial expressions. Nevertheless, the test-retest reliability of high-resolution facial sEMG is not analyzed in detail yet, as good reliability is a necessary prerequisite for its repeated clinical application. Methods: 36 healthy adult participants (53% female, 18-67 years) were included. Electromyograms were recorded from both sides of the face using an arrangement of electrodes oriented by the underlying topography of the facial muscles (Fridlund scheme) and simultaneously by a geometric and symmetrical arrangement on the face (Kuramoto scheme). In one session, participants performed three trials of a standard set of different facial expression tasks. On one day, two sessions were performed. The two sessions were repeated two weeks later. Intraclass correlation coefficient (ICC) and coefficient of variation statistics were used to analyze the intra-session, intra-day, and between-day reliability. Results: Fridlund scheme, mean ICCs per electrode position: Intra-session: excellent (0.935 to 0.994), intra-day: moderate to good (0.674 to 0.881), between-day: poor to moderate (0.095 to 0.730). Mean ICC's per facial expression: Intra-session: excellent (0.933 to 0.991), intra-day: good to moderate (0.674 to 0.903), between-day: poor to moderate (0.385 to 0.679). Kuramoto scheme, mean ICC's per electrode position: Intra-session: excellent (0.957 to 0.970), intra-day: good (0.751 to 0.908), between-day: moderate (0.643 to 0.742). Mean ICC's per facial expression: Intra-session: excellent (0.927 to 0.991), intra-day: good to excellent (0.762 to 0.973), between-day: poor to good (0.235 to 0.868). The intra-session reliability of both schemes were equal. Compared to the Fridlund scheme, the ICCs for intra-day and between-day reliability were always better for the Kuramoto scheme. Conclusion: For repeated facial sEMG measurements of facial expressions, we recommend the Kuramoto scheme.